Pelanggaran Pidana oleh Notaris: Urgensi Peningkatan Kesadaran dan Pemahaman Etika Profesi (Lembaga Pengembangan Kinerja Dosen, 2025)
The regulation of notarial professional ethics is still often neglected, as reflected in the numerous ethical violations especially those related to criminal acts committed by notaries. This research aims to examine the criminal acts of notaries and the urgency of enhancing professional ethical awareness as a preventive measure. The research method is descriptive-analytical with a normative juridical approach. The study’s results show that there are still many notaries who commit criminal offenses, usually involving embezzlement, fraud, and forgery. The ethical awareness becomes an important factor to prevent criminal acts by notaries. This emphasizes the importance of a deep understanding of ethical codes as part of a notary's identity, where these rules are not merely written but must also be implemented in every professional action.